2007
DOI: 10.1039/b616582f
|View full text |Cite
|
Sign up to set email alerts
|

Acyl palladium species in synthesis: single-step synthesis of α,β-unsaturated ketones from acid chlorides

Abstract: Conditions are reported for the facile, one-pot synthesis of alpha,beta-unsaturated ketones via the palladium-catalysed cross-coupling of acyl chlorides with hydrozirconated acetylenes, and its use in the 2-step synthesis of D-5-O-benzyl deoxyxylulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
176
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(179 citation statements)
references
References 19 publications
3
176
0
Order By: Relevance
“…Interestingly, 1-epi-bacillisporin F (3) was also isolated. 1 H NMR data revealed that the sole differences between compound 2 and 3 were the chemical shifts of the methoxy group in CD3OD…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 1-epi-bacillisporin F (3) was also isolated. 1 H NMR data revealed that the sole differences between compound 2 and 3 were the chemical shifts of the methoxy group in CD3OD…”
Section: Resultsmentioning
confidence: 99%
“…1 These complex structures have attracted great interest because of their biological activities which may lead to new medicinal or agrochemical applications. Soil-inhabiting fungi constitute an extremely diverse fungal community and the soil fungus Talaromyces stipitatus ATCC 10500 (syn.…”
mentioning
confidence: 99%
“…1A) (18,19), the carbon scaffold of radicicol is synthesized by the collaborative functions of two type I iterative polyketide synthases (IPKSs). IPKSs are megasynthases in which linearly juxtaposed catalytic domains function in an iterative and a highly programmed fashion (20). Genetic knock-out experiments with two different radicicol-producing fungi, Pochonia chlamydosporia and Chaetomium chiversii (16,21), confirmed that a highly reducing PKS (HRPKS) and a nonreducing PKS (NRPKS) are required for the biosynthesis of radicicol.…”
mentioning
confidence: 88%
“…Fungal PKSs are large megasynthases that assemble single copies of catalytic domains in one polypeptide. The domains function in an iterative fashion and use built-in programming rules to dictate chain length, cyclization, reductive tailoring, and other structural features (11). Therefore, understanding the relationships between protein sequence and catalytic activity, as well as substrate specificity, of each domain is essential to unlocking the biosynthetic potential of fungal PKSs.…”
mentioning
confidence: 99%